Intralesional Vitamin D Injection May Be an Effective Treatment Option for Warts - Aktas, Habibullah; Ergin, Can; Demir, Betul; Ekiz, Ozlem (Sage Publications Inc, 2016)
Background: Plantar warts are typically resistant to treatment. In recent years, treatments have included administration of intralesional tuberculin; measles, mumps, rubella vaccine; and Candida albicans antigen immunotherapy. To the best of our knowledge, there are no reports of intralesional vitamin D administration for the treatment of warts. Aim: To evaluate the efficacy and safety of intralesional vitamin D treatment for plantar warts. Methods: Twenty patients with single or multiple plantar warts were included in this study. Vitamin D-3 (0.2 mL, 7.5 mg/mL) was injected into the base of the warts after prilocaine (0.1 mL, 20 mg/mL) injection. A maximum of 5 warts were treated in 1 session, with at maximum 2 injections performed at 4-week intervals. Results: In total, 16 of 20 patients (80%) showed complete resolution of warts, and 1 patient showed partial resolution. Three patients failed to show any response. No recurrence or serious adverse effects were observed. Conclusion: Intralesional vitamin D-3 may be an effective treatment option for warts.
Keywords: viral warts; vitamin D injection; treatment